NIMG-72. PROGNOSTIC VALUE OF [18F]-FDG POSITRON EMISSION TOMOGRAPHY IN PATIENTS WITH RECURRENT GLIOBLASTOMA RECEIVING BEVACIZUMAB. (11th November 2019) - Graham, Maya; Krebs, Simone; Bale, Tejus; Domfe, Kwaku; Lobaugh, Stephanie; Zhang, Zhigang; Dunphy, Mark; Kaley, Thomas; Young, Robert
Abstract: BACKGROUND: Bevacizumab is used extensively for the treatment of recurrent glioblastoma, and its modification of contrast-enhanced MRI creates a need for alternate prognostic read-outs. We sought to determine the prognostic value of [ 18 F]-FDG (FDG) PET in glioblastoma patients performed during treatment with bevacizumab. METHODS: We performed an institutional review board approved retrospective study on patients who underwent FDG PET within 4 weeks of a dose of bevacizumab for recurrent glioblastoma. Volumes of interest were placed over one reference lesion as defined by MRI. Maximum standardized uptake value (SUVmax) and peak standardized uptake value (SUVpeak) in this volume of interest were measured on PET, and metabolic tumor volume (MTV), total lesion glycolysis (TLG) and lesion-to-normal contralateral white matter ratios (SUVmax/cWM) were calculated. In addition, tumors were divided into 2 groups based on qualitative uptake pattern: (i) FDG non-avid and (ii) FDG avid. Statistical impact of PET parameters on overall survival (OS) was assessed, as was histopathological correlate of PET findings for patients with pathology available within 3 months of PET. RESULTS: 31 patients were included. Qualitative uptake pattern was significantly associated with OS ( p = 0.005), with a median OS of 9.7 months in FDG non-avid patients versus 4.5 months in FDG avid patients. In univariate analysis, SUVmax, SUVpeak and T/N ratio were also significantly associated with OS (p < 0.001). Dichotomizing our sample using a SUVmax cut-off of 15.3 was also predictive of OS (adjusted p = 0.05). Pathology was available for 7 patients (22.6%) and confirmed PET findings. CONCLUSION: FDG PET is a promising imaging biomarker to predict overall survival in recurrent glioblastoma patients on chronic antiangiogenic therapy, offering a tool for guiding assessment of treatment response in this patient population.